Implementation of the ChatGPT-based Question and Answer Method in Improving Student Arabic Communication Skills - Fridayanti, Andita Aprilia; Khusna, Qothrunnida Khayatul (Maharaat: Jurnal Pendidikan Bahasa Arab, 2024)
The development of technology has influenced various aspects of life, especially in education. The use of ChatGPT in the educational realm has provided remarkable benefits and opportunities for learning Arabic. This research is a qualitative study aimed at understanding the planning, utilization, and evaluation of ChatGPT as a media tool in Arabic language learning for seventh-grade students. Data collection techniques used in this study include observation, interviews, documentation, and questionnaires. The results indicate that the use of ChatGPT is highly suitable for Arabic language learning, as it enhances communication and student interest. This is evidenced by questionnaire results showing that 84% of 34 students felt that ChatGPT helped them improve their comfort and confidence in learning Arabic. Thus, with the use of ChatGPT, students are more enthusiastic and engaged in Arabic language learning.